Gold price prediction using an evolutionary pi-sigma neural network - Dash, Rajashree; Routray, Anuradha; Rautray, Rasmita; Dash, Rasmita (International Journal of Engineering and Technology, 2018)
Gold Price Prediction has always been a fascinating area of study for researchers and decision makers who wish to determine its future value efficiently and accurately. In this study a predictor model is designed using a Pi-Sigma Neural Network (PSNN) for prediction of future gold price. Two evolutionary estimation paradigms such as Particle Swarm Optimization (PSO) and Differential Evolution (DE) are suggested during training step of the Pi-Sigma Neural Network to optimize the tunable weights of the network. The model is evaluated based on certain performance evaluation criteria such as Mean Square Error (MSE), Root Mean Square Error (RMSE) and Mean Absolute Error (MAE) over two dataset such as Gold/INR and Gold/AED accumulated within the same period of time. The result analysis illustrates the better prediction
Keywords: Time Series Prediction; Pi-Sigma Neural Network; PSO; DE.